Focusing of baroclinic tidal energy in a canyon. Issue 4 (24th April 2016) - Vlasenko, Vasiliy; Stashchuk, Nataliya; Inall, Mark E.; Porter, Marie; Aleynik, Dmitry
Abstract: Strong three‐dimensional focusing of internal tidal energy in the Petite Sole Canyon in the Celtic Sea is analyzed using observational data and numerical modeling. In a deep layer (500–800 m) in the center of the canyon, shear variance was elevated by an order of magnitude. Corresponding large vertical oscillations of deep isotherms and a local maximum of horizontal velocity were replicated numerically using the MITgcm. The elevated internal tidal activity in the deep part of the canyon is explained in terms of the downward propagation and focusing of multiple internal tidal beams generated at the shelf break. The near‐circular shape of the canyon head and steep bottom topography throughout the canyon (steeper than the tidal beam) create favorable conditions for the lens‐like focusing of tidal energy in the canyon's center. Observations and modeling show that the energy focusing greatly intensifies local diapycnal mixing that leads to local formation of a baroclinic eddy. Key Points: Generation of internal tide in a circular canyon Focusing of baroclinic tidal energy in canyon center Generation of a baroclinic eddy due to diapicnal mixing